Rekognisi Moderasi Beragama terhadap Penganut Kepercayaan di Indonesia - Tungkagi, Donald Qomaidiasyah (Program Studi Tadris Ilmu Pengetahuan Sosial (TIPS) UIN Datokarama Palu, 2023)
This article wants to answer the question, is it possible for religious moderation to accommodate believers? This stems from the fact that believers in Indonesia are still often discriminated against in social life. Various programs and policies have been attempted, but this phenomenon continues as if it is endless. On the other hand, religious moderation as a state policy is challenged to be a solution to the problem. Using a library research method, reinforced by Otto Scharmer's Iceberg Analysis and U-Process (Unity in Diversity), this research tries to explore the layers that influence the phenomenon of discrimination against believers. In the first stage, the sociological divide will explore patterns & trends that include attitudes, behaviors, and habits that can be seen. The structure divide will explore the causal structures including traditions, culture, regulations, policies, government systems, etc. The spiritual-psychological divide will explore mental models that include paradigms, perspectives, and mindsets. The second stage starts with rethinking the mental model by changing the paradigm, followed by redesigning policies, structures, etc. The contribution of this research is to explore the root causes of the phenemona (event) of discrimination against believers, and to offer new action solutions (reacting) based on these issues to overcome the problem of intolerance and discrimination against belief groups in society.